The Influence of Locus of Control, Organization Citizenship Behavior and Work's Life Quality to Employee's Performance - Artiningsih, Dwi Wahyu; Rasyid, Syahdi (Jurnal Aplikasi Manajemen, 2013)
This research is to evaluate: (1) the influence of locus of control to employee’s performance, (2) the influence of organization citizenship behavior to employee’s performance and (3) the influce of work’s life quality to employee’s performance. The population is taken from 40 respondents by using stratified random sampling and data is analysed by PLS (partial least square). The research reveals that (1) locus of control doesn’t influence employee’s performance, (2) organization citizenship behavior influences employee’s performance and (3) quality of work’s life influences employee’s performance. Locus of control doesn’t influence employee’s performance indicates that employess of this hospital - RSUD Kotabaru are not able to develop locus of control both internally and externally in order to create competitive work condition and inedequate efforts are taken to encounter problems, in that it will be overcome in a better manner and have outstanding performances.